2018
DOI: 10.1007/s00464-018-6341-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of short-term outcomes between laparoscopic and open emergent repair of perforated peptic ulcers

Abstract: Emergent laparoscopic repair of perforated peptic ulcer is increasingly being performed, is safe relative to open repair (in patients without preoperative septic shock), and confers a modest benefit in terms of length of stay, respiratory, and abdominal wall wound complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
1
12
0
1
Order By: Relevance
“…Although multiple studies have demonstrated the benefits of repairing PPUs laparoscopically, in our study, it was associated with longer operative duration (Laparoscopic 117.1 ± 35.6 min, open 85.6 ± 41.8 min, p = 0.01), which is comparable to other studies [ 17 , 20 ]. This may be explained by the fact that there is improved exposure and more efficient mobilization in open repair.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Although multiple studies have demonstrated the benefits of repairing PPUs laparoscopically, in our study, it was associated with longer operative duration (Laparoscopic 117.1 ± 35.6 min, open 85.6 ± 41.8 min, p = 0.01), which is comparable to other studies [ 17 , 20 ]. This may be explained by the fact that there is improved exposure and more efficient mobilization in open repair.…”
Section: Discussionsupporting
confidence: 83%
“…These outcomes directly lead to decreased cost and increased patient satisfaction. The study by Davenport and colleagues [ 17 ] demonstrated that within the United States American College of Surgeons National Surgical Quality Improvement Project (ACS NSQIP) population, the proportion of laparoscopic PPU repairs has nearly tripled from 4.5% in 2010 to 11.4% in 2016 ( p < 0.001), indicating that more surgeons are utilizing the laparoscopic approach to repair PPUs. This can be attributed to generally decreased morbidity associated with laparoscopic surgery and increased study data pertaining to safety and efficacy of the technique, with improved postoperative outcomes including reduced surgical site infections, postoperative complications, and hospital length of stay [ 1 , 11 , 12 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Included studies were published between 1996 and 2019. Five were RCTs [14][15][16][17][18] , three were prospective cohort studies [19][20][21] , and the other 15 studies used retrospective cohort or case-control designs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] ( Table 1). All compared outcomes of laparoscopic versus open peptic ulcer repair.…”
Section: Resultsmentioning
confidence: 99%
“…The finding of surgical intervention for perforated ulcers is viewed as the mainstay of care, as noted by Lee et al 14 Specifically, the use of a laparoscopic approach with an experienced surgeon in stable patients is supported by a meta-analysis performed by Cirocchi et al 15 that found the laparoscopic approach to primarily reduce postoperative pain in the first 24 hours, and reduce postoperative wound infection compared to an open approach for perforated peptic ulcer repair. Similarly, a retrospective review by Davenport et al 16 reports reduced length of stay, decreased mortality and renal insufficiency, and improved respiratory function for patients without preoperative shock who were treated for perforated peptic ulcer using the laparoscopic approach compared to an open approach.…”
Section: Delay In Interventionmentioning
confidence: 95%